On Perceptions of Criminal Justice in Society - Dobryninas, A.; Dobrynina, M.; Česnienė, I.; Giedraitis, V.; Merkevičius, R. (Sociologija. Mintis ir veiksmas, 2012)
Abstract. The perception of criminal justice in society is a controversial social problem. Traditionally, criminal justice issues have been treated as a matter of professional interest for criminologists, criminal justice experts and other professionals from related fields. But is expert knowledge the only valid kind when it comes to criminal justice topics? This question, though rhetorical, is aimed at stimulating discussion about the co-existence of different types of social knowledge on criminal justice, and their impact on various discourses concerning crime and punishment in society. In this article a group of researchers from Vilnius University makes use of phenomenological methods to analyse three different types of discourse on criminal justice: professional, political and public. The professional discourse on criminal justice is scrutinised from the perspective of penal law, the political discourse from the point of view of macroeconomics, while the public discourse is analysed using ideas drawn from psychology and media studies. The analysis of these discourses seeks to examine the social construction of criminal justice, and the particularities of its reception among professionals, politicians and a wider public.Keywords: criminal justice, discourses, economic circles, psychological reception, mass media.